(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In the article, in a series of articles published in our national press at the beginning of the 20th century, the issue of granting the status of the state language to our Jadid language and Muzayyana Alaviya’s "A few words about our language", Behbudi’s "Address to the youth: Not two, four languages are needed", Said Ahrari "Dictionary and spelling column", Ismailbek Gasprinsky "Language and spirituality", Fitrat’s articles "Language and spirituality" and "Let’s move to the Latin alphabet" held.